Dissociation of agency and body ownership following visuomotor temporal recalibration - Imaizumi, Shu; Asai, Tomohisa (Frontiers in Integrative Neuroscience, 2015)
Bodily self-consciousness consists of one’s sense of agency (I am causing an action) and body ownership (my body belongs to me). Both stem from the temporal congruence between different modalities, although some visuomotor temporal incongruence is acceptable for agency. To examine the association or dissociation between agency and body ownership in the context of different temporal sensitivities, we applied a temporal recalibration paradigm, in which subjective synchrony between asynchronous hand action and its visual feedback can be perceived after exposure to the asynchronous visuomotor stimulation. In the experiment, participants continuously clasped and unclasped their hand while watching an online video of their hand that was presented with delays of 50, 110, 170, 230, 290, and 350 ms. Then, they rated a video of their hand with a delay of 50 ms (test stimulus) with respect to the synchrony between hand action and hand video and the perceived agency over the video. Moreover, proprioceptive drift of participants’ hand location toward the hand video during the exposure was measured as an index of illusory body ownership. Results indicated that perception of agency emerged over the delayed hand video as subjective visuomotor synchrony was recalibrated, but that body ownership did not emerge for the delayed video, even after the recalibration. We suggest that there is a dissociation between agency and body ownership following visuomotor temporal recalibration.